Unlocking Hidden Treasures Through Description: Comments on Archival Voyages of Discovery - Pederson, Ann (Archivaria, 1994)
After reviewing a decade of steady work and discussion about standards for archival description across three continents, this paper urges us to pause for a few moments to reflect on our accomplishments and to reassess our goals, resources, and methodologies. In pursuing standardization, we voyage towards a predetermined "destination"–to reveal the heretofore unknown riches of archives so that they may be made accessible for responsible and appropriate use. But our existing methods for reaching that destination may not be as serviceable as we contend. To make the most of this process, we must be adaptable, alert to dogmatism, and accepting of our own foibles. Only then can we confidently seize and exploit the many opportunities that the unfolding journey will certainly bring. RÉSUMÉ Après avoir passé en revue une décennie de débats et de travail ininterrompu dans trois continents à propos des normes de description, cet article propose un temps d’arrêt afin de réfléchir sur nos réalisations et de réévaluer nos buts, nos ressources et nos méthodologies. En recherchant la normalisation, nous nous engageons pour une destination prédéterminée, pour révéler les trésors des archives jusqu’ici inconnus afin de les rendre propres à une utilisation responsable et appropriée. Cependant, nos méthodes actuelles pour atteindre cette destination peuvent ne pas être aussi solides que nous le prétendons. Afin de tirer le meilleur parti de ce processus, nous devons être capables d’adaptation, vigilants envers le dogmatisme et accepter nos propres marottes. Alors seulement pourrons-nous saisir et exploiter avec optimisme les nombreuses chances qu’offrira le parcours.